Analisis Batimetri Guna Perencanaan Pengerukan Kolam Pelabuhan Kalibaru Tanjung Priok Menggunakan Single Beam Echosounder - Tribhuwana, Awliya; Abdurrahman, Farid (Jurnal Civil Engineering Study, 2023)
The Kalibaru Port of Tanjung Priok, North Jakarta, is one of the ports that is used for shipping and loading and unloading activities. Bathymetry information is needed to support one of the activities in the port, namely in terms of shipping. The purpose of this research is to map the bathymetry in the harbor pool area and to find out the areas that need to be dredged in the Kalibaru Tanjong Priok harbor pond. This research was conducted on May 24, 2022 in the pond area of ​​Tanjung Priok Harbor, North Jakarta. This research was conducted using a single beam echosounder using a Garmin GPSmap 420s tool to determine the depth of the harbor pool. Data processing using Ms. excel, Auto CAD land desktop, surfer to generate depth contours and calculate dredge volume. The volume calculation uses the average end area method. The calculation result of dredging volume is the sum of the cross-sectional area multiplied by the section distance. The results showed that the depth of the Tangjung Priok harbor waters ranged from 3 to 17 meters and the dredged volume reached 165,319 m3.